Study on the Performance in the Sector of Production, Processing and Preserving White Meat from Romania, a Member of the European Union - Ciprian Apostol (CES Working Papers, 2017)
In the context that consumption of white meat is increasingly recommended for a healthy diet, the study aims to highlight the main features of the performance in the manufacturing, processing and preserving sector of white meat in Romania. In this direction, the scientific approach was based both on a qualitative and the quantitative approach of the issues studied and the methods of analysis were descriptive and comparative. In order to better highlight the evolution of the performance in this sector was compared the national sector and the European one and the time frame for analysis is between the years 2008-2015, i.e. the period during the financial crisis and the after.
Keywords: M49; O14; Q22; 330; performance; white meat; food industry; Romania; European Union